Pembuatan Asam Mangga Sebagai Upaya Meningkatkan Nilai Ekonomi Mangga di Desa Kanje Sulawesi Barat - Syamsuri, Syamsuri; Alang, Hasria; Hafsah, Hafsah (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The abundance of mangoes during the harvest season, and the sour taste of the mangoes even though they are ripe and perishable in nature, the people of Kanje Village process the mangoes into sour. This tamarind is called Kaloko and is a mandatory spice used by the people in making Mandarese food, namely the smell of peapi. The problem found is that the mango acid produced is black in color making it less attractive and unfit for marketing. In fact, it is not uncommon to find that the acid that has been made is also moldy when stored for a long time. Overcoming this problem, the PKM team offers a solution to provide education and training on making mango tamarind which is attractive in color and resistant to fungus. The PKM method used is observation, education and practice of making mango tamarind. This activity was carried out in the homes of residents who often make mango sour. The PKM was carried out on Saturday, April 22, 2023, then the evaluation of the final result of mango acid was carried out on Tuesday, April 25, 2023. The results of the PKM showed that the community was able to produce attractively colored mango acid. This shows that this PKM activity has been successful because it is proven to be able to improve partners' skills.